Preparation of mixed matrix membrane using cellulose acetate incorporated with synthesized KIT-6 silica - Ding, S.H. (Universiti Malaysia Pahang, 2018)
There is increasing interest among researchers to develop Mixed Matrix Membranes (MMMs), by incorporating fillers in polymer membranes. However, these membranes always suffer from a trade-off between permeability and selectivity as proven by Robeson in upper bound curves developed in gas separation applications. In current project, mesoporous silica, KIT-6 was synthesized and followed by incorporation of KIT-6 as filler into cellulose acetate (CA) matrix to form MMMs. The fabrications of MMMs were done by using dry phase inversion method. The KIT-6 loadings in the MMMs were varied from 2 to 10 wt. The properties of KIT-6 and membranes were characterized with Scanning electron microscopy (SEM), Fourier transform infrared (FTIR), X-ray diffraction (XRD) and thermal gravimetric analysis (TGA). The effect of KIT-6 loadings on the properties of the formed MMMs was investigated. XRD and FTIR results suggested that KIT-6 mesoporous silica is successfully synthesized. The TGA curve indicate the overall weight loss of 3.02 for KIT-6 and 72.29-86.77 for all the membranes. The successful incorporation of silica particles into CA polymer matrix is confirmed by FTIR spectrum while MMMs images from SEM suggested that KIT-6 silica powder could embed well with CA polymer matrix. Defect-free MMMs could be fabricated and potential to be use in future especially in gas separation. Â© Universiti Malaysia Pahang, Malaysia